2017
DOI: 10.1063/1.4977063
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origins of high multilevel resistive switching in forming free Ti/TiO2−x-based memory devices through experiments and simulations

Abstract: Although multilevel capability is probably the most important property of resistive random access memory (RRAM) technology, it is vulnerable to reliability issues due to the stochastic nature of conducting filament (CF) creation. As a result, the various resistance states cannot be clearly distinguished, which leads to memory capacity failure. In this work, due to the gradual resistance switching pattern of TiO2−x-based RRAM devices, we demonstrate at least six resistance states with distinct memory margin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…However, the deviation from the ohmic character especially at low I cc , indicates that the presence of space charges, such as oxygen vacancies, imposes a different conduction mechanism. On the other hand, HRS is fitted quite well by TAT mechanism (see Figure (d)), which has been presented in our previous work . The fitting of the various states can be performed by increasing only the ionic component of the TAT mechanism, while the electronic component is not seriously affected.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…However, the deviation from the ohmic character especially at low I cc , indicates that the presence of space charges, such as oxygen vacancies, imposes a different conduction mechanism. On the other hand, HRS is fitted quite well by TAT mechanism (see Figure (d)), which has been presented in our previous work . The fitting of the various states can be performed by increasing only the ionic component of the TAT mechanism, while the electronic component is not seriously affected.…”
Section: Resultssupporting
confidence: 72%
“…The various switching patterns can be interpreted by calculating the electrical conductivity from the oxygen vacancy density ( n d ), using the following equation: σtrue(nnormaldtrue)=σ0exptrue(Enormalαtrue(nnormaldtrue)knormalBTtrue) where σ 0 is a pre‐exponential factor, E α ( n d ) is the activation energy, k B is the Boltzmann constant, and T is the absolute temperature. The results that are presented in Figure (a) indicate a threshold value of oxygen vacancy density which determines the boundary between TAT and ohmic conduction mechanism, while an almost linear function was selected for E α ( n d ) . As it can be seen from Figure (b), n d value is of great importance, since small variations in n d < n TAT region can cause large variability in the various desired multilevel states, due to the non‐linear dependence of the electrical conduction pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these films show poor switching as shown in figure 3(c), where the incomplete switching of the initial plot may be attributed to the incomplete movement of oxygen vacancies due to the short duration of the switching voltage application. On the contrary, Au-contacted titania thin films formed by other methods have been reported to show filamentary resistive switching with high switching ratios [29][30][31][32][33][34]. A plausible explanation of this difference is a lower expected density of oxygen vacancies in nanosheet-derived films.…”
Section: Resultsmentioning
confidence: 98%
“…Electron spectroscopy techniques such as X-ray photoelectron spectroscopy (XPS) have been implemented in order to chemically address memristive characteristics. 13,17,18 XPS has been predominantly used to investigate the composition of memristive devices or to carry out ex situ measurements where devices are excited prior to XPS measurements. Similar to this effort, a recent study reported in situ measurements using X-ray photoelectron emission microscopy (PEEM) to detect valence change in TaO x devices during switching.…”
Section: Introductionmentioning
confidence: 99%